2020
DOI: 10.1177/0003134820964227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pelvic Anastomosis by Endoscopic and Contrast Studies Prior to Ileostomy Closure: Are Both Necessary? A Single Institution Review

Abstract: Contrast enema is the gold standard technique for evaluating a pelvic anastomosis (PA) prior to ileostomy closure. With the increasing use of flexible endoscopic modalities, the need for contrast studies may be unnecessary. The objective of this study is to compare flexible endoscopy and contrast studies for anastomotic inspection prior to defunctioning stoma reversal. Patients with a protected PA undergoing ileostomy closure between July 2014 and June 2019 at our institution were retrospectively identified. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In prior large series, when strictures were identified based on the existence of symptoms alone, anastomotic stricture rates were reported in the range of 5-10%. [1][2][3][4][5]9 Among studies which examined anastomoses endoscopically, there is variability in the size of scope used and therefore how strictures were defined. [1][2][3][4][5]8,10 Authors have previously demonstrated that there is no clear correlation between degree of stricture and clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In prior large series, when strictures were identified based on the existence of symptoms alone, anastomotic stricture rates were reported in the range of 5-10%. [1][2][3][4][5]9 Among studies which examined anastomoses endoscopically, there is variability in the size of scope used and therefore how strictures were defined. [1][2][3][4][5]8,10 Authors have previously demonstrated that there is no clear correlation between degree of stricture and clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…143 Similarly, in a retrospective study that compared 91 patients with low pelvic anastomoses who underwent flexible endoscopy (FE) before ileostomy closure versus 100 patients who underwent both FE and contrast evaluation (CE) before reversal, there were no significant differences in the detection of pelvic anastomotic leak (2.2% versus 1%), anastomotic stricture (1.1% versus 6%), or postoperative anastomotic complications (4.4% versus 9%) between the groups. 146 Similar findings published in the setting of IPAA call into to question the routine use of preoperative pouchogram. A retrospective study of 52 pouch patients without immediate postoperative complications evaluated patients with a contrast study performed at a median of 14 weeks (range, 7-71 weeks) after IPAA and by an EUA on the day of the ileostomy closure.…”
Section: Routine Water-soluble Contrast Studies In the Absence Of A C...mentioning
confidence: 88%
“…143 Similarly, in a retrospective study that compared 91 patients with low pelvic anastomoses who underwent flexible endoscopy (FE) before ileostomy closure versus 100 patients who underwent both FE and contrast evaluation (CE) before reversal, there were no significant differences in the detection of pelvic anastomotic leak (2.2% versus 1%), anastomotic stricture (1.1% versus 6%), or postoperative anastomotic complications (4.4% versus 9%) between the groups. 146…”
Section: Ostomy Closurementioning
confidence: 99%
“…Most surgeons evaluate the rectal integrity with a contrast enema before reversal. However, the utility of this investigation has not been studied among trauma patients specifically and is controversial among patients undergoing ostomy reversal after elective resections despite historically being considered the gold standard investigation 24,25 . If there is any question about rectal integrity on contrast enema, or if the injury was particularly destructive, one can consider flexible sigmoidoscopy to visualize the area of injury and ensuring healing prior to stoma reversal.…”
Section: Algorithmmentioning
confidence: 99%